Corporate portals - Guruge, Anura (Digital Press, 2003)
Following the humbling of the 'dot.coms' it is well implemented corporate portals that are ushering in a new and prosperous era of e-business. Corporate Portals Empowered with XML and Web Services provides decision makers with a clear and concise explanation of what portals are all about, why you really need a portal strategy, how you go about implementing one, and the issues you have to encounter and surmount. Guruge shows how you can successfully use XML and web services to empower your portals for collaboration, knowledge management, CRM, ERP and supply chain management. Extensive examples of corporate portals illustrate the viability of the technology Architectural and network diagrams show detailed portal implementations Comprehensive references to guides, solutions, products and terminology leverage living outside resources.